1997
DOI: 10.1007/bf03162212
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Starburst Dendrimers and SDS micelles studied by continuous-wave and pulsed electron spin resonances

Abstract: A computer aided analysis of both cw-and pulsed-Electron Paramagnetic Resonance (EPR) spectra of 5doxylstearic acid (5DXSA) as a probe was carried out to compare the aggregation process of Sodium Dodecyl Sulfate (SDS) surfactants in the absence and in the presence of Starburst Dendrimers (SBDs), and to provide information on the interactions between SDS and SBDs. Mobility and polarity parameters were extracted from the cw-EPR analysis, whereas the analysis of the Eleetron Spin Echo Envelope Modulation (ESEEM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 39 publications
7
39
0
Order By: Relevance
“…Micro‐aggregate states of lyotropics have been modelled using SDS molecules. Previous experimental studies have suggested that due to the hydrophobic nature of the 5DSA spin probe, limited aggregation centred around the probe can occur below the critical micelle concentration …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro‐aggregate states of lyotropics have been modelled using SDS molecules. Previous experimental studies have suggested that due to the hydrophobic nature of the 5DSA spin probe, limited aggregation centred around the probe can occur below the critical micelle concentration …”
Section: Resultsmentioning
confidence: 99%
“…Previouse xperimental studies have suggested that due to the hydrophobic nature of the 5DSA spin probe, limited aggregation centred around the probe can occur below the critical micelle concentration. [74] By starting MD simulations with ar andom dispersion of up to five SDS molecules and one probe in as imulation box filled with water molecules, the formation of flexible micro-aggregates aroundt he spin probe was observed in < 10 ns (Figure 3a). In fact, SDS molecules did not form stable micro-aggregatese xcept in the presenceo f5 DSA.…”
Section: Resultsmentioning
confidence: 99%
“…Amphiphilic probes, bearing the paramagnetic unit along the alkyl chain, have been extensively employed to obtain information on the dynamics and ordering at the molecular level within aggregates such as micelles and natural or synthetic lipid membranes [18,19,[21][22][23][24][25][29][30][31][32][33][34][35][36][43][44][45][46][47][48]. Here, we used CAT-12, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[7] The interactions of a cationic surfactant at the dendrimer=water interface of half-generation dendrimers [6] and an anionic surfactant with the surface of full-generation dendrimers have been shown to be feasible. [3,4,8] In contrast to previous studies that have observed surfactant aggregation on dendrimer surfaces, [8][9][10][11][12] in this work we focus on supramolecular structures with electrostatic interactions involving a maximum of one surfactant per dendrimer terminal group. Also, in contrast with earlier studies, [4] we show that the positioning of a guest molecule within the dendrimer-surfactant supramolecular complex can be modulated by using surfactants of varying alkyl chain length, varying dendrimer generation, and varying surfactant concentration.…”
Section: Introductionmentioning
confidence: 91%